Analysis of Risk Factors for Increased Intraocular Pressure in Phacoemulsification Surgery: Single Center Study in Jakarta, Indonesia - Hambali, Nadya; Syukri Mustafa (HM Publisher, 2024)
Background: Phacoemulsification, a common cataract surgery technique, can increase intraocular pressure (IOP) postoperatively. This study aimed to identify risk factors contributing to increased IOP, focusing on patient age and duration of phacoemulsification. Methods: A cross-sectional study was conducted at Harapan Jayakarta Hospital, Jakarta, for 4 months (May-September 2023) on 43 cataract patients ≥40 years old who underwent phacoemulsification. Inclusion criteria were preoperative IOP 10-21 mmHg, clear conjunctival and corneal structures. Data analysis was carried out univariate and bivariate using SPSS. Results: Analysis showed a significant correlation between patient age and phacoemulsification duration (older patients = longer phacoemulsification time), with a mean age of 63.21 years. Phacoemulsification duration >270 seconds significantly increases the risk of postoperative IOP. Conclusion: Prolonged exposure to ultrasonic waves during phacoemulsification can cause cellular injury to the internal structures of the eye, increasing IOP. Identifying modifiable risk factors, such as optimizing phacoemulsification timing, may reduce these complications and improve cataract surgery outcomes.